The ecology and population dynamics of the Nile crocodile Crocodylus niloticus in the Flag Boshielo Dam, Mpumalanga province, South Africa - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2006.